2015
DOI: 10.1002/pam.21811
|View full text |Cite
|
Sign up to set email alerts
|

Can Genetics Predict Response to Complex Behavioral Interventions? Evidence from a Genetic Analysis of the Fast Track Randomized Control Trial

Abstract: Early interventions are a preferred method for addressing behavioral problems in high-risk children, but often have only modest effects. Identifying sources of variation in intervention effects can suggest means to improve efficiency. One potential source of such variation is the genome. We conducted a genetic analysis of the Fast Track Randomized Control Trial, a 10-year-long intervention to prevent high-risk kindergarteners from developing adult externalizing problems including substance abuse and antisocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 94 publications
1
52
1
Order By: Relevance
“…Greater attention must be paid to how information about the unfolding of genetic risk across adolescence, in conjunction with the environment, can be used to inform prevention and intervention. Although some investigators have begun to explore these questions (Albert et al, 2015; Brody et al, 2013; Dodge et al, 2013; Dodge and McCourt, 2010), this remains an important area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Greater attention must be paid to how information about the unfolding of genetic risk across adolescence, in conjunction with the environment, can be used to inform prevention and intervention. Although some investigators have begun to explore these questions (Albert et al, 2015; Brody et al, 2013; Dodge et al, 2013; Dodge and McCourt, 2010), this remains an important area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid receptor activation in brain regions such as the amygdala and hippocampus regulates the function of the hypothalamic-pituitary-adrenal (HPA) axis, which regulates circulating cortisol levels in humans. 63 The NR3C1 transcript is highly expressed in the amygdala relative to other brain tissues during the first trimester (Supporting Information, Figure SS1). 57,58 NR3C1 promoter methylation predicts NR3C1 expression and associates with altered HPA responses to stress and effects on neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that not all children benefit equally from intervention, and a growing number of studies demonstrate that intervention effectiveness varies as a function of genotype (Albert et al , 2015, Bakermans-Kranenburg & Van Ijzendoorn, 2011, Brody et al , 2013). For example, one study found that children who were more biologically sensitive to stress (as indexed by carriers of one or two copies of A allele of a variant of NR3C1 , a glucocorticoid receptor gene) had higher rates of externalizing behaviors in the control condition and lower rates of externalizing behaviors in the intervention condition in the Fast Track project (Albert et al, 2015). Many of these studies have focused on candidate genes (e.g., Bakermans-Kranenburg et al , 2008; Beach et al ., 2010), and, thus are interesting more from a proof of principle standpoint at this time.…”
Section: Post-gwas Areas Of Exploration From a Developmental Perspectivementioning
confidence: 99%